Seed Quality Selection of Several Genotypes of Brown Rice (Oryza sativa L.) under High-Temperature Stress - Afrima Sari; Indra Dwipa; Aswaldi Anwar; Irfan Suliansyah; Netti Herawati (JERAMI : Indonesian Journal of Crop Science, 2022)
Climate change impacts increasing temperature, and environmental factors can affect the capacity and rate of seed germination. This study aimed to determine and study the effect of temperature changes on the viability and vigor of brown rice seeds and the morphology of the sprouts produced. The variation of temperature used was 28-400C, and ten genotypes of brown rice seeds used were Pulen Mudiak, Pulen Kandih, Pulen Marapak, Pulen Talao, 64, Sibandung, Silalang, Timbo Abu, Labuah Baru, and Melayu. The results showed that every 10C increase in temperature affects rice germination percentage. The optimum temperature for the germination of ten genotypes of brown rice tested was a temperature range of 28-330C, with a germination value of >80%, the maximum critical temperature 370C and at 38-40 0C no brown rice seeds germinated. Pulen Marapak has the highest maximum growth potential of 90,3% at 280C and 10% at 370C. The increase in temperature also damages brown rice roots and shoots dengan the average root length is 6,7-10,1 cm and shoot length is 8-11,5 cm at 280C.